Associations of adolescent menstrual symptoms with school absences and educational attainment: analysis of a prospective cohort study - Gemma Sawyer; Abigail Fraser; Deborah A. Lawlor; Gemma C. Sharp; Laura D. Howe (npj Science of Learning)
Abstract Menstrual symptoms may negatively impact academic achievement, but rigorous population-based studies are lacking. 2,698 participants from the Avon Longitudinal Study of Parents and Children (ALSPAC) self-reported heavy or prolonged bleeding and menstrual pain during adolescence and multivariable regression were used to estimate associations with linked data on absences and attainment at age 15/16, adjusting for confounders. Heavy or prolonged bleeding and pain were associated with missing 1.7 (16.58% increase) and 1.2 (12.83% increase) additional days of school per year, respectively, and 48% and 42% higher odds of persistent (≥10%) absence. Heavy or prolonged bleeding was associated with lower examination scores (−5.7 points) and 27% lower odds of achieving five standard passes. The association between pain and attainment was weaker but still present (−3.14 points; 95% CI: −7.46, 1.17; 16% lower odds of five standard passes). Greater research and support are needed to prevent adolescents’ menstrual symptoms impacting their academic achievement.